Comprehensive assessment of the speech development of children conceived by IVF - K. L. Surkova; N. V. Zvereva; A. A. Sergienko; S. E. Strogova; M. V. Zvereva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The high frequency of the use of assisted reproductive technologies and the inconsistency of information about the parameters of the cognitive development of IVF children determined the formulation of the research problem.The purpose of the work is to assess the originality of the speech development of children and adolescents conceived using the IVF procedure. The age of the children at the time of the survey was from 5 to 15 years.Methods and materials. A sample of 51 children (29 boys), mean age (7.9±2.8) years, 14 children had psychiatric diagnoses (ASD, mental retardation, etc.). Research methods: speech therapy assessment of speech development, neuropsychological diagnostics according to L.S. Tsvetkova, WICS, descriptive statistics, correlation analysis.Results. 41% of children had mild variants of speech development delay under 3 years old, 59 % of children had normal speech development. With age, the frequency of detected deviations in speech development decreases, so that in older age group (from 11 to 15 years old), 85 % have normotypical development of speech. Correlation analysis showed the originality of the correlations of the parameters of speech development, neuropsychological assessment, and scores on Wechsler subtests.Conclusions. An unambiguous conclusion about the violation of speech development in children conceived by IVF cannot be drawn, however, in the presence of mental pathology and taking into account the age of the mother and the number of ART procedures, attention should be paid to the provision of speech therapy and neuropsychological correction from an early age.